Students’ Use of Graphs in Understanding the Concepts of Derivative - Haliza Abd Hamid; Noraini Idris; Ruzela Tapsir (Southeast Asian Mathematics Education Journal, 2019)
Previous research showed that visual utilisation in mathematics classrooms help students in understanding concepts. This study was conducted to assist educators in realising visual reasoning skills in students which can be employed in classroom practices as the students move to their higher levels of education. The study is part of a larger project. It studied 194 pre-university students’ perception of the use of graphs and examined their actual ability to extract information embedded in the graphs in order to understand and solve derivative problems. Findings showed that students were very encouraged to use graphs in the teaching and learning of mathematics but the opposite was evident in their worked solutions. Implications of teaching and learning are also discussed.